Sistem Pendukung Keputusan Untuk Penjurusan di SMAN 1 Ampek Angkek Kab. Agam dengan Metode Multifactor Evaluation Process (MFEP) - Randa Mahardika; Rini Sovia; Shary Armonitha Lusinia (Universitas Negeri Padang, 2017)
SMA N 1 Ampek Angkek is one of the high school International Standard. Therefore it takes a Human Resources (HR) superior, quality, and achievement in the field of education for majors prospective students / new student should be based on the criteria in accordance with the standard expected. In this study will be designed a system of computerized decision support to assist the school in majors prospective students / new student. Decision Support System (DSS) is the alternative system application that helps a decision in the majors prospective students / new student at SMA N 1 Ampek Angkek Kab. Agam using Multifactor Evaluation Process (MFEP). Multifactor Evaluation Process (MFEP) is a decision-making process by giving instuitif and subjective consideration of the criteria involved and considered important so that trend is happening is a failure that match the criteria.